PENGARUH MODEL PEMBELAJARAN KOOPERAIF TIPE STUDENT TEAMS ACHIEVEMENT DEVISION (STAD) TERHADAP KEMAMPUAN BERPIKIR KRISTIS SISWA PADA PEMBELAJARAN MATEMATIKA KELAS IV SD - Febrina Turnip; Sinta D Simanjuntak; Nova Florentina ambarwati; Bogor Lumbanraja; Heka Maya Sari Sembiring; Patri Janson Silaban (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the effect of using the Student Teams Achievement Devision (Stad) type cooperative learning model on student learning outcomes in the material Building Rooms, Cubes and Blocks for class IV SD 067093 Medan Helvetia in 2023/2024. This type of research is quantitative using the one group pretest-posttest design method. The population of this study were all fourth grade students at SD 067093 Medan Helvetia who were studied in one class totaling 23 students. Sampling was taken using saturated sampling and a sample of 23 students was obtained. Based on the results of this research, it shows that the student learning outcomes before doing it where 21 students did not complete with a percentage of 91.30% and 2 students completed with a percentage of 8.69% which was obtained from the average pretest score of 53.26, and after using the learning model Cooperative Type Student Teams Achievement Devision (Stad) shows that student learning outcomes are in the very good category with an average of 80.21, where 20 people have a completion percentage of 89.95% and 3 students who get scores below the average (mean) have percentage 13.04%. The results of this research show that the correlation test results can be seen in the correlation coefficient value of 0.698, meaning Tcount (0.698) > Ttable (0.361), so ha is accepted, so there is a strong influence between the learning model and the influence of using the cooperative learning model. Type Student Teams Achievement Division (Stad) on student learning outcomes can also be seen from the results of the t-test where tcount > ttable, namely 7.617 > 2.080, thus stating that the Ha hypothesis is accepted. This shows that there is an influence of the Student Teams Achievement Division (Stad) cooperative learning model on student learning outcomes in the material Building Cubes and Blocks for class IV SD 067093 Medan Helvetia in 2023/2024.